Vliv směsí "Green solvents" a nanočástic na vybrané polymerní povrchové úpravy - Trhlíková, Lucie (Vysoké učení technické v Brně. Fakulta chemická)
Práce je zaměřena na studium směsí rozpouštědel typu "green" a nanočástic při interakci s vybranými polymerními povrchovými úpravami. Hodnotí se odolnost povrchových úprav proti účinku směsí rozpouštědel s přídavkem přípravků s nanočásticemi a odstranitelnost vybraných nečistot z povlaků typu polyvinylchlorid, polyuretan a polyester pomocí rozpouštědel na bázi směsných esterů.

This work is aimed to the study of mixtures of solvents type "green" and nanoparticles in direct interaction with selected polymeric surface treatment. The values in question are resistance of surface treatment to effect of solvent mixtures with additions of nanoparticles agents and removability of selected impurities from coating layers of polyvinyl chloride, polyurethane and polyester by solvents of the basis of mixed esters.
Influence of „Green solvents“ and nanoparticles mixtures on select polymeric surface finishing.
Keywords: Nanočástice; povrchová úprava; povlak; polymer; polyvinylchlorid; polyester; polyuretan; rozpouštědlo; odolnost.; Nanoparticles; finish; coating; polymer; polyvinylchloride; polyester; polyuretane; solvent; resistance.